(untitled) - Canington, Deborah K. (Australia, 2006)
This book is used to accompany the second edition of Plant biology by Thomas Rost, Michael Barbour, C Ralph Stocking. It consists of 27 exercises following the Plant biology text topic sequence. The exercises focus on plant cell types and plant body organization; plant energy and water movement in plant body, flowering plants; the concept of a life cycle and basic life cycle differences and meiosis and ecology. The book survey organisms from bacteria through seed plants
Keywords: Botany,Thực vật học